Making Filipino values work for you - Andres, Tomas Quintin D.; Ilada-Andres, Pilar Corazon B. (Makati City, Philippines : St. Paul Publications, 1986)
The purpose of this book is to help you, to develop a safe and sound understanding, appreciation, and action on your filipino self, that you may bring out the best in the Filipino soul and put that best into use.
Part One. Know your filipino self -- Part Two. Know your filipino characteristics -- Part Three. Know your filipino values -- Part Four. Know how to communicate -- Part Five. Know how to optimize your resources -- Part Six. Know how to become an entrepreneur, reach the top, and retire successfully.
Includes bibliographical references.
Keywords: VALUES -- FILIPINO